Efficacy of Probiotics, Cetylpyridinium Chloride, and Enzymes Toothpaste Formulations Against Periodontal Pathogens in Fixed Orthodontic Patients: A Review - Michelle; Harryanto Wijaya; Joko Kusnoto (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: Fixed orthodontic appliances complicate oral hygiene and promote biofilm accumulation, increasing the risk of periodontal disease. Toothpaste formulations with antimicrobial properties such as Lactobacillus paracasei probiotics, cetylpyridinium chloride (CPC), and amyloglucosidase–glucose oxidase enzymes are commonly used to manage oral biofilm and control pathogenic bacteria. However, the extent of their effectiveness against periodontal pathogens in orthodontic patients remains unclear. Purpose: This review aims to map and summarize the current evidence on the efficacy of various toothpaste formulations in reducing periodontal pathogens among patients undergoing fixed orthodontic treatment. Methods: A comprehensive search of electronic databases (e.g., PubMed, Scopus, Google Scholar) was conducted to identify relevant studies published from 2015 to 2025. Data were extracted and synthesized narratively, focusing on types of formulations, study outcomes, and microbial targets. Results: Formulations containing antimicrobial agents such as probiotics, enzymes, and cetylpyridinium chloride showed variable effects on specific periodontal pathogens, including Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans. Each mechanism antimicrobial, probiotic, and enzymatic addresses different aspects of biofilm regulation. Conclusion: Toothpastes containing L. paracasei probiotics, CPC, and amyloglucosidase–glucose oxidase enzymes offer complementary ways to control periodontal pathogens in orthodontic patients. Combining these mechanisms may enhance biofilm control and microbial balance, though further research is needed to confirm their long-term benefits.